In-orbit test and error analysis of shaped-reflector antenna pattern via satellite's attitude offset. (1st January 2014) - He, Yuan-zhi; Yin, Shu-yi; Wang, Jing-chao
In order to accurately test the satellite's shaped-reflector antenna pattern and efficiency in orbit, an in-orbit test method of the antenna pattern via satellite's attitude offset and the shaped beam forming principle is proposed. Key points of the method testing the antenna patterns are the edge of roll-off, side-lobe suppression, weighted region and level fluctuation performances, etc. By discussing the relationship between the satellite's offset angle and the test point's longitude and latitude, the proposed method employs the error analysis and testing data correction which combined with the compact test range data. Test results show that the radiation performance of satellite's antenna is stable.